2015
DOI: 10.3923/ppj.2015.158.167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some Treatments on Seed Health and Viability of Soybean

Abstract: A B S T R A C TThis study was carried out in order to evaluate effect of treating soybean seed (Glycin max L.) as seed coating with fungicidal (Vetavax-thiram 200), seed dressing with biotic (Bio-arec, Bio-zeid) and seed soaking with abiotic (Salicylic acid) in controlling fungal diseases and improving seed and seedlings vigor of cultivars (Giza 21, G.35, G.111, G.22, G.82, Klark, Crawford) . The obtained results showed that, Alternaria spp., Aspergillus spp., Cercospora kikuchii, Diaporthe sojae, Fusarium mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Generally, soil amendment with these bio-control products was effective in decreasing Fusarium wilt disease symptoms on tomato plants. These results are consistent with those reported by Ibrahim (2015) showed that application of biocides (Bio-Arc and Bio-Zeid) as seed dressing reduced percentage of mean infection seedborne fungi such as Alternaria spp., F. moniliforme, F. semitectum, F. solani, F. oxysporum and Rhizoctonia solani. In this study, Bio-Arc showed higher effect in reducing percentage of disease severity of tomato wilt.…”
Section: Discussionsupporting
confidence: 93%
“…Generally, soil amendment with these bio-control products was effective in decreasing Fusarium wilt disease symptoms on tomato plants. These results are consistent with those reported by Ibrahim (2015) showed that application of biocides (Bio-Arc and Bio-Zeid) as seed dressing reduced percentage of mean infection seedborne fungi such as Alternaria spp., F. moniliforme, F. semitectum, F. solani, F. oxysporum and Rhizoctonia solani. In this study, Bio-Arc showed higher effect in reducing percentage of disease severity of tomato wilt.…”
Section: Discussionsupporting
confidence: 93%
“…However, treatments T4 and T5 significantly reduced infection of A. flavus infection as compared to other treatments irrespective of seed storage in cloth bag or polythene bag. Ibrahim (2015) also found that soybean treated seeds with vitavax-200 eliminate Aspergillus spp completely and improve seedling vigour characteristics. Upreti (2013) found an increase in Aspergilllus flavus infection of maize seeds stored in cloth bag.…”
Section: Resultsmentioning
confidence: 89%
“…Soybean is known as one of the crucial oil crops all over the world (Ibrahim, 2015). Soybean (Glycine max L.), which is summer and annual plant, has been the most valuable food source of Far East countries such as China and Korea for nearly 4500 years.…”
Section: Introductionmentioning
confidence: 99%